Evolution and industry trend of 5G key technologies - Jing CHONG; Xiaoyong TANG; Lei ZHU; Na LI; Jue ZHANG; Zhengpeng YOU; Peike XU; Jia LIU (Dianxin kexue)
With the further integration of 5G and the industry, the current standard-defined Release 15/Release 16/Release 17 capabilities were slightly insufficient to support industry needs.The technological evolution direction of 5G-Advanced (Release 18) was reviewed in detail, and potential technical solutions for the technological evolution were given, including downlink MIMO enhancement, uplink transmission enhancement, mobility enhancement, topology transmission technology enhancement, Sidelink enhancement, RedCap technology evolution, positioning capability expansion and enhancement, AI/ML 5G, etc.At the same time, the current industry scene was analyzed in detail, those existing problems including industry terminal access, access network, E2E QoS guarantee, etc.The 5G technologies including SLA-based industry networking, high out-of-band (OOB) suppression, multi-buffer scheduling (MBS), fully connected industry access network technology, computing force network (CFN) technology, and potential implementation methods were proposed.